Damping identification in a stress-ribbon footbridge - Álvaro Cunha (2005)
This paper describes the different types of dynamic tests (hammer, shaker, free and ambient vibration tests) recently performed on the stress-ribbon footbridge of FEUP Campus, with the purpose of achieving an accurate identification of the most significant modal parameters, getting better sensitivity with regard to the advantages and drawbacks associated to the application of the alternative identification techniques employed. Due to the enormous influence that damping has on the structural simulated response under pedestrian loads, particular attention has been dedicated to the identification of modal damping factors.